Understanding climate action by teenagers as social movements : A case study of Youth 4 Climate Action in Korea - Lee,Hyerim (Master Thesis Series in Environmental Studies and Sustainability Science, 2020)
This thesis is about Y4CA, a youth organization in Korea for climate action. It discusses how non-teenagers support teenage activists for the sustained climate action by considering three factors for social movement: political opportunities, mobilizing structure and framing process by adding collective identity. By using mixed methodology, a survey about behavioral factors of teenagers, in-depth interviews with activists, researchers, educators, and government agencies and focus group interviews with teenage activists- it investigates issues they are struggling with and studies inclusive solutions. Political opportunities allow youth climate action to emerge, though most teenagers are prevented from making use of these political opportunities. In addition, every behavior by teenagers has been regarded as a ‘spec’: the requirement to apply for university. Simultaneously, consuming the image of youth, youth-washing, happens due to the demand for teenage voices for political diversity. This hinders the development of social networks. Also, there are conflicts regarding membership after Y4CA expand their working group in December 2019 because of because of the decision-making system led by old members, absence of shared cognitive definition without active relationship, and emotional investment. Moreover, there are some limitation for mobilizational framing from recognition of teenagers as stupid or underaged, government targeted action and one-way media use. Therefore, it is recommended 1) increasing political opportunities for more teenager by alternative education and valid political rights 2) Re-building collective identity for membership and social network by slack organization and providing platforms, 3) motivational framing considering credibility, audience effect and using online media. Climate action by teenage activists is important because teenagers are the generation directly involved with the impact of the climate crisis, citizens of society at present, and intellectuals who will lead the future. To sustain youth climate action as a social movement, it is necessary for other generations to be in solidarity with Y4CA as an equal citizen, rather than helping. It is common in the world that the climate crisis is connected to generation justice, most teenagers are in students' positions, and a general gap exists. So, this research is meaningful and valid for other cases of youth climate action globally. In conclusion, for the success of youth climate action as a social movement stimulating society as the counter-hegemony, it is important to consider teenage activists’ actions seriously and respond to their demands by recognizing teenagers as equal citizens, not as a student.
Keywords: Youth climate action; Youth participation; Political opportunity; Mobilizing structure; Framing process; Collective identity; Sustainability Science